Peridynamic State-Based Models and the Embedded-Atom Model (Communications in Computational Physics, 2014)
We investigate connections between nonlocal continuum models and molecular dynamics. A continuous upscaling of molecular dynamics models of the form ofthe embedded-atom model is presented, providing means for simulating moleculardynamics systems at greatly reduced cost. Results are presented for structured andstructureless material models, supported by computational experiments. The nonlocalcontinuum models are shown to be instances of the state-based peridynamics theory.Connections relating multibody peridynamic models and upscaled nonlocal continuum models are derived.